2021
DOI: 10.1186/s12978-021-01098-8
|View full text |Cite
|
Sign up to set email alerts
|

Physician–patient communication in decision-making about Caesarean sections in eight district hospitals in Bangladesh: a mixed-method study

Abstract: Background Caesarean sections (CS) in Bangladesh have risen eight-fold in the last 15 years. Few studies have explored why. Anecdotally, physicians suggest maternal request for CS is a reason. Women and families suggest physicians influence their decision-making. The aim of this research was to understand more about the decision-making process surrounding CS by exploring physician–patient communication leading to informed-consent for the operation. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…In both cases, there was a lack of communication between the physicians and the patients and the family members of the patient. This study mirrored the findings of similar studies in Bangladesh that reported minimal communication between patients and physicians during C-section decision-making in healthcare facilities [37]. In 2012, a study reported that, in the Dhaka slums, for more than 50% of cases, the physician was the primary decision-maker for C-sections, and for 37% of cases, family members were also involved with C-section decision-making [38].…”
Section: Discussionsupporting
confidence: 82%
“…In both cases, there was a lack of communication between the physicians and the patients and the family members of the patient. This study mirrored the findings of similar studies in Bangladesh that reported minimal communication between patients and physicians during C-section decision-making in healthcare facilities [37]. In 2012, a study reported that, in the Dhaka slums, for more than 50% of cases, the physician was the primary decision-maker for C-sections, and for 37% of cases, family members were also involved with C-section decision-making [38].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, almost all caesarean section takes place in health facilities, which accounts for over 60% of the institutional deliveries in Bangladesh [ 76 ]. High rates of caesarean section in Bangladesh have been associated with previous maternal experience in caesarean section, high risk pregnancies, complications during labour, and maternal or physician preferences [ 77 , 78 ]. This highlights the need to address early initiation of breastfeeding practices in a post-caesarean section setting, and design interventions that facilitate early initiation of breastfeeding among women who had a health facility-based delivery [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been more significant increases in some countries. For instance, in Bangladesh [ 17 ], the CS rate increased eight-fold from 2004 to 2017/8 with a four-fold increase in Nepal [ 12 , 18 ] between 2001 and 2011, with this trend continuing [ 12 , 17 - 18 ]. Previous studies found that CS delivery was higher among urban women, primarily educated women, than rural, uneducated women [ 9 , 11 , 18 - 22 ].…”
Section: Introductionmentioning
confidence: 99%